2000
DOI: 10.1046/j.1365-3156.2000.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ICT whole blood antigen card test to detect infection due to nocturnally periodic Wuchereria bancrofti in South India

Abstract: SummaryThe commercially available ICT Card Test for bancroftian filariasis was evaluated for its sensitivity and specificity in detecting microfilaria carriers among 189 individuals each in filariasis-endemic and nonendemic areas in South India, and compared to both conventional night blood finger prick thick blood smear examination and venous blood membrane filtration. Though the specificity of the test was 100% in comparison to both, the sensitivity was 98.5% against the finger prick thick blood smear and 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 12 publications
(27 reference statements)
0
25
0
Order By: Relevance
“…Some studies evaluating the whole blood ICT card test in the field have been performed 6,12,15,17 . However, most of them involve two-stage samples which commonly introduce bias that may affect both sensitivity and specificity estimates 20,23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies evaluating the whole blood ICT card test in the field have been performed 6,12,15,17 . However, most of them involve two-stage samples which commonly introduce bias that may affect both sensitivity and specificity estimates 20,23 .…”
Section: Discussionmentioning
confidence: 99%
“…These significant features make the whole blood ICT card test a potential diagnostic tool to be adopted in screening and surveillance of bancroftian filariasis risk areas. However, studies evaluating this new test in fieldwork are still scarce 6,12,15,17 and the study designs applied can place some limitation on the applicability of these results to different groups of individuals 20,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Within each village, 50 adult males above 15 years of age, and 40 households were selected for estimating antigenemia prevalence within the community using the ICT card test. 26,27 The number of households (40) to be sampled per village was based on the finding that on average in rural India 2 to 3 adult males would be available per household; the selection of households themselves was performed by first listing the total number of households in the village followed by estimating the sampling interval (total number of households/40) for the systematic selection of household units for the study. The first household is selected randomly (by choosing a number randomly between one and the sampling interval), and the others are chosen by the cumulative addition of the sampling interval to each previous number as described elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…This investigation forms part of a multicountry study initiated by the World Health Organization (WHO) Rapid Geographical Assessment of Bancroftian Filariasis (RAGFIL) program, 25 which advocated using a sampling grid of either 25 × 25 km or 50 × 50 km for selecting communities to undertake rapid filariasis prevalence surveys (by the application of rapid assessment procedures (RAP) surveys of filariasis prevalence, such as physical examination by the health workers (PEHW) 26 or estimation of parasite antigenemia prevalence by the use of the immunochromatographic card test (ICT) 27 to map and investigate filariasis distribution. While the primary analysis is based on filariasis antigeneamia prevalence data obtained from 79 communities selected from an endemic region in South India using the 25 × 25 km grid sampling framework, comparison is also made with the spatial structure of microfilaraemia prevalence data obtained from a random sample of 119 villages within the same region (used for a separate study validating different RAP methods 26 ), to illustrate the importance of spatial sampling scale for the detection and quantification of spatial structure.…”
Section: Introductionmentioning
confidence: 99%
“…There were 11 positive samples by PCR, but negative by ICT. All the 11 samples however, had 0 to 10 microfilaria counts per ml, for which ICT may have missed because it has low sensitivity (11,12). The advantages of the PCR assay used in this study include high sensitivity, specificity and demonstrated a high accuracy value of 94.4%.…”
Section: Discussionmentioning
confidence: 99%